Pengaruh Pemberian Probiotik pada Infeksi Clostridium Difficile - Ade Dharmawan; Dhimas Garin Dewa Agista; Sinsanta Sinsanta; Nicolas Layanto; Deby Deby (Jurnal MedScientiae, 2022)
Clostridium difficile (C. difficile) is a gram-positive, anaerobic, spore-forming bacterium, and is an important pathogen in antibiotic-associated diarrhea. These bacteria are normal flora in the human digestive tract but can become pathogenic and form toxins consisting of 2, namely toxin A and toxin B. Due to antibiotics including risk factors for C. difficile infection (CDI), the treatment that can be given is probiotics. Probiotics may be effective in the prevention and treatment of CDI in several ways: alteration of gut flora, enhancement of antimicrobial activity, and as immunomodulators. The effect of probiotics, the method of administration, and the varying duration of administration make probiotics unable to be used as a therapy for C. difficile infection. However, probiotics can still be an option for adjuvant therapy in the treatment of CDI.